Prevalence of daytime sleepiness and internet addiction among college going students in Bangalore - Kumaar, Arun R.; S., Usha; Manjunatha, Shashikala; C., Chandrakala (International Journal Of Community Medicine And Public Health, 2026)
Background: In recent years, the dual burden of excessive internet use and daytime sleepiness has emerged as a growing concern among college students. Balancing academic responsibilities with prolonged screen time often disrupts sleep patterns and affects students’ overall well-being. Methods: A cross-sectional study was conducted among 280 college students in Bangalore. Data were collected using two validated tools: the Epworth sleepiness scale (ESS) to assess daytime sleepiness, and Young’s Internet addiction test (IAT) to evaluate internet usage patterns. The data were entered into Microsoft excel and analyzed using SPSS version 23. Descriptive statistics were used to present frequencies and percentages, and chi-square tests were applied to determine associations. Results: Of the 280 participants, 180 were female and 100 males. The ESS results showed that 10 students (3.5%) had pathological daytime sleepiness, while 121 (43.2%) had normal levels. The IAT revealed that 47 (16.7%) students had moderate internet addiction, 69 (24%) had mild addiction, and 165 (59%) used the internet appropriately. A statistically significant association was found between internet addiction and daytime sleepiness (Chi-square=25.8, p<0.05). No significant association was found between gender and either internet addiction or daytime sleepiness. Conclusions: A considerable proportion of college students in Bangalore experience internet addiction and daytime sleepiness. The significant correlation between the two underscores the need for awareness programs and interventions promoting healthy sleep and responsible internet use among students.